2017
DOI: 10.1111/acel.12597
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage and senescence in osteoprogenitors expressing Osx1 may cause their decrease with age

Abstract: SummaryAge‐related bone loss in mice results from a decrease in bone formation and an increase in cortical bone resorption. The former is accounted by a decrease in the number of postmitotic osteoblasts which synthesize the bone matrix and is thought to be the consequence of age‐dependent changes in mesenchymal osteoblast progenitors. However, there are no specific markers for these progenitors, and conclusions rely on results from in vitro cultures of mixed cell populations. Moreover, the culprits of such cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
131
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(148 citation statements)
references
References 63 publications
(75 reference statements)
13
131
0
Order By: Relevance
“…The functional role of ROS in age-dependent bone loss has been demonstrated by attenuation of the age-related decline in femoral cortical thickness by overexpression of catalase in cells of the osteoblast lineage (23). Finally, other studies of ours suggest that senescence of osteoblast progenitors leading to cell cycle arrest increases with age, which may contribute to the reduction in the number of endosteal osteoblasts (69).…”
Section: Discussionsupporting
confidence: 54%
“…The functional role of ROS in age-dependent bone loss has been demonstrated by attenuation of the age-related decline in femoral cortical thickness by overexpression of catalase in cells of the osteoblast lineage (23). Finally, other studies of ours suggest that senescence of osteoblast progenitors leading to cell cycle arrest increases with age, which may contribute to the reduction in the number of endosteal osteoblasts (69).…”
Section: Discussionsupporting
confidence: 54%
“…Interestingly, this was due to arrest at the G1 phase of the cell cycle . Moreover, osteoprogenitors from old mice exhibited several characteristics of senescent cells, including elevated levels of γH2AX foci (a marker of DNA damage due to double‐strand breaks), phosphorylated p53, elevated p21 expression, and upregulation of several SASP factors such as GATA4 and activation of NF‐κB . Complementary to these findings in osteoprogenitors, Farr and colleagues found upregulation of several SASP factors with aging, predominantly in enriched populations of myeloid cells and osteocytes.…”
Section: Cellular Senescencementioning
confidence: 87%
“…(66,8690) Last, targeted apoptosis of senescent cells with so-called senolytic agents restores tissue homeostasis in response to chemotoxicity and aging and attenuates atherosclerosis and posttraumatic osteoarthritis. (71,72,9193) …”
Section: The Development Of Drugs Targeting Mechanisms Of Aging and Tmentioning
confidence: 99%
“…(72) They found that it decreases GATA4 expression and improves the ability of osteoprogenitors to differentiate into bone-forming osteoblasts. Moreover, it attenuates the senescence-associated secretory phenotype and the ability of osteoprogenitors to support osteoclast formation.…”
Section: The Development Of Drugs Targeting Mechanisms Of Aging and Tmentioning
confidence: 99%
See 1 more Smart Citation